MENGUKUR DAMPAK PENERAPAN PRESIDENTIAL THRESHOLD DI PEMILU SERENTAK TAHUN 2019 - Diniyanto, Ayon (Indonesian State Law Review (ISLRev), 2018)
The implementation of the 2019 Election and the stages of its implementation cannot be separated from various issues or polemics. Many polemics occur starting from the regulatory side, general implementation, up to technical matters. The birth of new regulations related to the Election was colored by a polemic of the presidential threshold. Law Number 7 of 2017 concerning General Elections as a single regulation at the law level in organizing Elections cannot be separated from controversy. Many people respond to the pros and cons. The pros and cons response is focused on several things, one of which is the presidential threshold. The polemic or pros and cons associated with the presidential threshold in the community actually contain big question marks. First, the big question is whether the presidential threshold contained in Law Number 7 of 2017 concerning General Elections is in accordance with the constitution? considering the law is a translation of the constitution. Second, is the presidential threshold set forth in Law Number 7 of 2019 in accordance with the wishes of the community or not detrimental to the community? considering the law is aimed at regulating the aspirations of the community.